2005
DOI: 10.1093/jac/dki148
|View full text |Cite
|
Sign up to set email alerts
|

Linezolid for the treatment of multidrug-resistant tuberculosis

Abstract: In our experience, linezolid has been a valid alternative drug in the management of multidrug-resistant tuberculosis. The prolonged use of linezolid is frequently associated with toxicity, mainly anaemia and peripheral neuropathy, that requires special management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(126 citation statements)
references
References 33 publications
1
120
0
5
Order By: Relevance
“…18,19 Study characteristics for the 11 included studies are summarised in Table 1. [10][11][12][20][21][22][23][24][25][26][27] A total of 218 patients received linezolid, of whom 148 had evaluable outcomes; the remainder were reported to have been still receiving treatment at the time of publication. All patients were adults, and all were infected with MDR-TB, of whom at least 62 (28%) were infected with XDR-TB strains.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 Study characteristics for the 11 included studies are summarised in Table 1. [10][11][12][20][21][22][23][24][25][26][27] A total of 218 patients received linezolid, of whom 148 had evaluable outcomes; the remainder were reported to have been still receiving treatment at the time of publication. All patients were adults, and all were infected with MDR-TB, of whom at least 62 (28%) were infected with XDR-TB strains.…”
Section: Resultsmentioning
confidence: 99%
“…More than 40% of patients in this cohort received offlabel treatment against MDR or XDR TB with the oxazolidinone linezolid (28). In vitro and pharmacogenetic data suggest that oxazolidinones could be useful in management of mycobacterial infection, including MDR TB (29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and pharmacogenetic data suggest that oxazolidinones could be useful in management of mycobacterial infection, including MDR TB (29)(30)(31)(32). However, clinical experience with the use of linezolid in the management of mycobacterial infections has been mainly restricted to case reports in nontuberculous mycobacterial diseases (33)(34)(35) and to a few case reports on patients with MDR TB (28,36,37). Cases of 24 patients with mycobacterial infections who were treated with linezolid were recently reviewed (38).…”
Section: Discussionmentioning
confidence: 99%
“…Its MIC for M. tuberculosis is 0.125-1 µ g/ml (Alcala et al 2003). It has been reported that 100 mg/kg once daily appeared to be bacteriostatic or weakly bactericidal, causing an approximately 1~1.5 log reduction in bacterial counts over 28 days, and that 600 mg linezolid orally twice daily in salvage regimens for MDR-TB was associated with sputum culture conversion and cure, albeit with frequent dose-or treatment-limiting side effects such as anaemia, thrombocytopenia, and peripheral or optic neuropathy (Fortun et al 2005; Von der Lippe et al 2006). Linezolid acts as an inhibitor of bacterial ribosomal protein synthesis.…”
Section: Oxazolidinone (Linezolid)mentioning
confidence: 99%